1989
DOI: 10.1111/j.1540-8159.1989.tb02648.x
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Left Free‐Wall and Posteroseptal Accessory Atrioventricular Pathways by Direct Recording of Accessory Pathway Activation

Abstract: With the advent of catheter ablation techniques, precise localization of accessory AV pathways (AP) assumes greater importance. In an effort to define the course of AP fibers, we attempted to record activation of 56 left free-wall and 23 posteroseptal APs in 62 patients undergoing electrophysiological study. The coronary sinus (CS) and great cardiac vein (GCV) were mapped using orthogonal catheter electrodes, which provide a recording dipole perpendicular to the AV groove. The tricuspid annulus (TA) was mapped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(27 citation statements)
references
References 26 publications
2
24
0
1
Order By: Relevance
“…block.32 The absence of an increase in the ventriculoatrial interval may be explained by the observation that, in almost half of the patients with "posteroseptal" accessory pathways, accessory pathway potentials are recorded across the tricuspid anulus rather than from the coronary sinus. 29 The demonstration of significant lateral excursion in left free-wall accessory pathways seems consistent with what is known of the embryological development of the heart at the AV boundary. In the primitive, fused cardiac tube, circumferential rings of histologically distinct specialized tissue have been described that later contribute variously to the cardiac fibroskeleton and the several divisions of the specialized cardiac conduction system.33-38 In the course of looping of the primitive cardiac tube, the common atrial region migrates upward and posteriorly, coming to lie above and behind the primitive ventricle and bulbus cordis.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…block.32 The absence of an increase in the ventriculoatrial interval may be explained by the observation that, in almost half of the patients with "posteroseptal" accessory pathways, accessory pathway potentials are recorded across the tricuspid anulus rather than from the coronary sinus. 29 The demonstration of significant lateral excursion in left free-wall accessory pathways seems consistent with what is known of the embryological development of the heart at the AV boundary. In the primitive, fused cardiac tube, circumferential rings of histologically distinct specialized tissue have been described that later contribute variously to the cardiac fibroskeleton and the several divisions of the specialized cardiac conduction system.33-38 In the course of looping of the primitive cardiac tube, the common atrial region migrates upward and posteriorly, coming to lie above and behind the primitive ventricle and bulbus cordis.…”
Section: Resultssupporting
confidence: 67%
“…Viable islets of anatomic continuity along with developing left AV groove would then presumably be subject to the effects of torsion upon growth and would exhibit counterclockwise rotation from atrium to ventricle as viewed from the apex. As part of the developmental expansion of the primitive ventricle and bulbus cordis at the time of bulboventricular folding, the previously circumferential myogenic fibers are pulled diagonally toward the vortex, which in turn migrates distally and comes to form the apical 22,25,27,29,45 …”
Section: Resultsmentioning
confidence: 99%
“…At fluoroscopy, the tip of the ablation catheter was seen to be in close proximity to the His‐bundle catheter. The septal region usually is defined as bounded superiorly by the His bundle and inferiorly by the roof of the coronary sinus 17 . Dividing this area into three parts, para‐Hisian APs occupy the superior third of this area (Figs.…”
Section: Methodsmentioning
confidence: 99%
“…Alternative energy forms, particularly radiofrequency current, may prove to be safer. This, coupled with more precise localization of the acces sory pathway using direct accessory pathwaypotential recordings, and approaching left sided pathways across the atrial septum or retrograde aortic arch/left ventricle catheter ization, may result in higher success [30]. Recently, Warin et al [52] have reported successful catheter ablation of accessory pathways utilizing a direct approach and DC energy in 32 of 35 patients.…”
Section: Catheter Ablationmentioning
confidence: 99%
“…Accessory pathways may be most accu rately localized by the direct recording of an accessory pathway potential. This requires the use of catheters with closely spaced elec trode pairs [29,30],…”
Section: Localizing the Accessory Pathway(s)mentioning
confidence: 99%